Nurses' encounters with children in child and school health care: negotiated guidance within a given frame. Issue 3 (14th October 2013) - Golsäter, Marie; Enskär, Karin; Harder, Maria
<x xml:space="preserve">Abstract</x> Background Throughout childhood, children take part in health visits according to a health‐monitoring programme. The visits are aimed to promote the children's development and health and to strengthen them to take own responsibility for their health. Nurses' actions when encountering children at these visits are not explored to any great extent. Exploring nurses' actions can facilitate their reflections on their actions towards children and thereby promote children's involvement in such visits. Aim The aim of this study was to explore nurses' actions when encountering children at health visits. Method A qualitative explorative design, based on 30 video recordings of health visits in child and school health care, was used in this study. These visits were ordinary real‐life health visits. The data were subjected to qualitative content analysis. The right to conduct video recordings during health visits was approved by appropriate research ethics committees. Results The findings show that nurses, in order to carry out the health visits, encounter children through negotiated guidance. This guidance is understood as the process through which the nurses reach agreement with the children, and is comprised of directed and pliable strategies. At one moment, the nurse can use a directed strategy to inform the child and at the next moment a pliable strategy to provide the child space within the given frame, the health‐monitoring programme. By using these strategies intertwined, the nurse can provide the child space within the given frame and, at the same time, fulfil his/her responsibility to promote children's health and development. Conclusion The results highlight nurses' challenging and complex assignment of guiding children to promote their engagement in the health visits, thereby enabling the nurses to promote the children's health and development according to the national health‐monitoring programme.